2014
DOI: 10.1080/01635581.2014.939292
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Nutritional Support in Cancer Patients after Esophagectomy: 11 Years of Experience

Abstract: Esophageal cancer represents a high-risk group of patients. This study determines the association of artificial nutrition with morbidity, mortality, and survival and studies clinical situations that determine the choice between enteral (EN) and parenteral support (PN). This retrospective single-center study compared 2 periods: 1) treatment centered in surgical process with discretionary demand of support, and 2) elective therapeutic and nutritional interventions were systematized. Risks factors that determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…enteral/parenteral nutrition (EN/PN), immunonutrition, oral supplements, etc.) as well as the right time of feeding is a matter of controversy due to lack of consistent evidence for patients undergoing esophagectomy [9]. Special nutritional needs in the long run are also of great significance for patients with both resectable and unresectble disease, bearing in mind that the majority of these patients strive to meet their caloric and protein needs.…”
Section: Introductionmentioning
confidence: 99%
“…enteral/parenteral nutrition (EN/PN), immunonutrition, oral supplements, etc.) as well as the right time of feeding is a matter of controversy due to lack of consistent evidence for patients undergoing esophagectomy [9]. Special nutritional needs in the long run are also of great significance for patients with both resectable and unresectble disease, bearing in mind that the majority of these patients strive to meet their caloric and protein needs.…”
Section: Introductionmentioning
confidence: 99%
“…The leak rate tends to be higher if the colon conduit rather than gastric tube is used, and when it is placed in the anterior mediastinum rather than the posterior mediastinal route (1). Patients who succumb to complications following reconstruction surgery are typically of an advanced age, and necrosis of the esophageal replacement is a complication with an extremely high mortality rate (23)(24)(25). In the series of patients who were operated between January 2010 and December 2012, the incidence of mortality subsequent to coloplasty was 0%.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, approximately two thirds of the patients were in the advanced stage of the disease, with significant dysphagia, and nearly half of them had a BMI of <17 at the time of esophagectomy. Nutritional status and nutritional support, particularly by way of patients undergoing esophagectomy, are among factors that improve perioperative mortality rate and survival (23). Patients are at a higher risk of complications following coloplasty (8,24).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also suggested that patients may also benefit from oral feeding at the early stage after esophagogastrostomy (5,(15)(16)(17). There is sparse evidence suggested that parenteral nutrition has crucial effects in supplying energy and further improving physical health at the early stage after gastrointestinal surgery (18). Both the Chinese Medical Association and the International ERAS Society made a recommendation of early jejunal nutrition support after esophagectomy (14,19).…”
Section: Nutritional Statusmentioning
confidence: 99%